A novel intumescent flame-retardant to inhibit the spontaneous combustion of coal. (1st August 2021) - Yan, Bing-Rui; Hu, Xiang-Ming; Cheng, Wei-Min; Zhao, Yan-Yun; Wang, Wei; Liang, Yun-Tao; Liu, Tong-Yu; Feng, Yue; Xue, Di
Graphical abstract: Highlights: A novel environment-friendly and intumescent flame-retardant for coal's spontaneous combustion. The retardant has good efficiency in both low temperature and high temperature stages of coal's spontaneous combustion. Systematic analysis of the inhibitory mechanism of this intumescent flame-retardant during spontaneous combustion of coal. Abstract: The present paper proposes an intumescent flame-retardant, which is suitable for the entire process of spontaneous combustion of coal. Scanning electron microscopy (SEM), simultaneous thermal analysis, in situ FTIR, and temperature programmed experiment were adopted to analyze its inhibiting effect and mechanism. The results indicate that the flame-retardant can play good inhibitory effects during all stages of coal oxidation and decomposition. In the low-temperature stage of 30–120 °C, the flame-retardant carries a lot of water and the surface temperature of coal is reduced since the evaporation of water removes heat. Meanwhile, the hydroxyl groups in the flame-retardant can connect with the -COO- groups on the surface of coal through hydrogen bonds, and enhance the stability of coal. With the temperature increase, some interlamellar water molecules in Mg-Al-CO3 layered double hydroxides (LDHs) are removed, which reduces the surface temperature of coal. When the temperature is higher than 170 °C, the IFR/LDH undergoes alcholysis and expands, releasing a large amount of non-flammable gas to dilute the oxygen around coal. When the temperature reaches 300 °C, the expanded foam layer is carbonized and forms a porous char layer, thereby inhibiting the combustion. The CO release of coal sample with flame retardant reduces significantly. The temperature with the maximum weight loss rate increases by 50–70 °C, while the heat release reduces by 11.1–24.2%. After calcination at 500 °C for 30 min, the carbon residue is more than 1.6 times that of the untreated coal sample.